Injury incidence in a Spanish sub-elite professional football team: A prospective study during four consecutive seasons - Mallo, J.; Gonzalez, P.; Veiga, S.; Navarro, E. (Journal of Sports Science & Medicine, 2011)
The aim of this study was to investigate the injury incidence and injury characteristics of a Spanish sub-elite professional football team during four consecutive seasons. A team was followed prospectively from the season 2003-2004 to 2006-2007 and individual player exposure and time loss injuries were recorded during all club training sessions and matches. A total of 313 time-loss injuries were recorded. The mean injury incidence was 10.9 injuries/1000 hours (5.2 injuries/1000 training hours and 44.1 injuries/1000 match hours). The injury incidence during competitive matches was higher (p < 0.001) than in friendly matches (55.8 vs. 22.6 injuries/1000 hours). The incidence of major injuries (>28 days absence) was 0.4 injuries/1000 hours. The thigh was the most commonly (35%) injured region and caused 29% of all competitive match absence. Muscle injuries in the four main groups of the lower limbs (hamstrings, adductors, quadriceps and calf muscles) caused 43% of competitive match unavailability. The results of this study show that the risk to sustain a major injury in the course of the season was low for sub- elite footballers in comparison to elite players. Thigh strains were the first cause of absence in competition due to injury.